Socioeconomical analysis of goats and sheep exploitation in Piauí State, Brazil - Neto, José de Souza; Baker, Gregory A.; de Sousa, Francisco Beni (Pesquisa Agropecuaria Brasileira, 1995)
The objectives of this study were to characterize the goats and sheep production systems based on agri-socioeconomics parameters, to identify the factors related or not to the adoption of technologies, and to estimate the main factors affecting goats and sheep production in the Piauí State. The methodology was based on numerical descriptive analysis and on factorial analysis. The numerical descriptive analysis showed that the inhibiting factors to goats and sheep husbandry are related to the farm size, level of technology, credit, relations between research and extension, formal education and adverse environment. The results of the factorial analysis indicated that the five main factors are responsible for 56.6% of the total variation on the data from 118 farms, and 22 active variables. In the factorial analysis, the first factor explains 24.5% of the total variation, and the high coefficients of saturation related to goat (0.90060) and to sheep (0.8946) indicated that they are the main responsible for the increase of the small ruminant production in the Piauí State.